Movilidad estudiantil: entre la intención de integración de la educación superior y su mercantilización (2016)
After UNESCO’s 1998 World Declaration on Higher Education for the 21st Century, initiatives have arisen which prompt higher education institutions to focus their efforts on integration, cooperation and solidarity. A task that is frequently carried out through the internationalisation of higher education, especially by means of student mobility programs. Internationalisation in Latin America is the result of efforts based on relationships founded on trust. Motives for such programs vary, from the interest to access resources to the intention to tighten academic and research ties, where one can see an eagerness to achieve a higher international profile.